Westonci.ca is your trusted source for finding answers to all your questions. Ask, explore, and learn with our expert community. Get quick and reliable answers to your questions from a dedicated community of professionals on our platform. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.
Sagot :
To find the average rate of change of [tex]\( f(x) \)[/tex] over the interval [tex]\([-3, 2]\)[/tex], we will use the values of [tex]\( f(x) \)[/tex] at [tex]\( x = -3 \)[/tex] and [tex]\( x = 2 \)[/tex].
From the table, we have:
[tex]\[ f(-3) = -36 \][/tex]
[tex]\[ f(2) = 4 \][/tex]
The formula for the average rate of change of a function [tex]\( f(x) \)[/tex] over an interval [tex]\([a, b]\)[/tex] is given by:
[tex]\[ \text{Average rate of change} = \frac{f(b) - f(a)}{b - a} \][/tex]
Here, [tex]\( a = -3 \)[/tex] and [tex]\( b = 2 \)[/tex].
Substituting the values in the formula:
[tex]\[ \text{Average rate of change} = \frac{f(2) - f(-3)}{2 - (-3)} \][/tex]
Now, plug in the given values:
[tex]\[ \text{Average rate of change} = \frac{4 - (-36)}{2 - (-3)} \][/tex]
Simplify the expression by adding inside the numerator and subtracting in the denominator:
[tex]\[ \text{Average rate of change} = \frac{4 + 36}{2 + 3} \][/tex]
[tex]\[ \text{Average rate of change} = \frac{40}{5} \][/tex]
[tex]\[ \text{Average rate of change} = 8 \][/tex]
Therefore, the average rate of change of [tex]\( f(x) \)[/tex] over the interval [tex]\([-3, 2]\)[/tex] is:
[tex]\[ \boxed{8} \][/tex]
So, the correct answer is [tex]\( \text{C. 8} \)[/tex].
From the table, we have:
[tex]\[ f(-3) = -36 \][/tex]
[tex]\[ f(2) = 4 \][/tex]
The formula for the average rate of change of a function [tex]\( f(x) \)[/tex] over an interval [tex]\([a, b]\)[/tex] is given by:
[tex]\[ \text{Average rate of change} = \frac{f(b) - f(a)}{b - a} \][/tex]
Here, [tex]\( a = -3 \)[/tex] and [tex]\( b = 2 \)[/tex].
Substituting the values in the formula:
[tex]\[ \text{Average rate of change} = \frac{f(2) - f(-3)}{2 - (-3)} \][/tex]
Now, plug in the given values:
[tex]\[ \text{Average rate of change} = \frac{4 - (-36)}{2 - (-3)} \][/tex]
Simplify the expression by adding inside the numerator and subtracting in the denominator:
[tex]\[ \text{Average rate of change} = \frac{4 + 36}{2 + 3} \][/tex]
[tex]\[ \text{Average rate of change} = \frac{40}{5} \][/tex]
[tex]\[ \text{Average rate of change} = 8 \][/tex]
Therefore, the average rate of change of [tex]\( f(x) \)[/tex] over the interval [tex]\([-3, 2]\)[/tex] is:
[tex]\[ \boxed{8} \][/tex]
So, the correct answer is [tex]\( \text{C. 8} \)[/tex].
We appreciate your time on our site. Don't hesitate to return whenever you have more questions or need further clarification. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.